Quality of Health Services in Influencing Patient Satisfaction and Loyalty in Dental Clinics - Andi Muhammad Irfan M. Amir; Hasanuddin Thahir; Lenni Indriani; Fuad Husain Akbar; Eddy Heriyanto Habar; Irene Edith Rieuwpassa (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Quality of healthcare services plays a crucial role in determining the overall success of dental clinic operations. It influences not only treatment outcomes but also patients’ overall experiences and perceptions. Key elements such as staff friendliness, facility cleanliness, responsiveness to patient needs, and professional competence are essential factors that shape patient satisfaction and encourage long-term loyalty. These factors collectively determine how patients perceive service quality and whether they choose to return for future dental care. Methods: This study utilized a systematic review approach to explore the relationship between healthcare service quality and its influence on patient satisfaction and loyalty. Data were obtained from major academic databases, including PubMed, Google Scholar, and ScienceDirect. The PICO framework was applied to establish clear inclusion and exclusion criteria. Only articles published from 2019 onward that examined the influence of service quality on patient satisfaction and loyalty were selected. Each study was assessed for methodological quality and relevance. A total of five eligible studies were analyzed using the SERVQUAL model, which consists of five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Results: Findings revealed that all five SERVQUAL dimensions influenced patient satisfaction and loyalty, although to different extents. Tangibles, such as modern equipment and clean facilities, were important for creating comfort and a positive perception of care. However, reliability, responsiveness, assurance, and empathy demonstrated stronger and more consistent effects in enhancing both satisfaction and loyalty. Key factors such as personalized attention, professional staff behavior, timely service, and emotional support significantly contributed to positive patient experiences. Conclusion: The quality of dental healthcare services, particularly when addressing both technical and interpersonal aspects through the SERVQUAL framework, plays a crucial role in building patient satisfaction and loyalty. Clinics that invest in comprehensive quality strategies are better positioned to maintain long-term relationships with patients and improve service competitiveness.